Static in-plane shear behaviour of prefabricated wood-wool panel wallettes - Md Noh, M. S.; Ahmad, Z.; Ibrahim, A.; Kamarudin, A. F.; Mok, S. N. (2018)
The green construction material and technique are the current issue toward improving sustainability in the construction industry in Malaysia. The use of construction material that produced from renewable resources is a part of the effort for greening this industry. WWCP (Wood-wool cement panel) is a wood based product available to the construction industry to be used as a structural building wall element. This renewable material has the potential to replace the less eco-friendly materials such as bricks and other masonry element. However, the behaviour of wall subjected to the different load conditions is not well established and therefore, this study aimed to investigate the structural behaviour of the small scale wall (wallettes) subjected to in-plane lateral load. As a comparison, two types of fabrication technique of wallettes with dimension of 1200 mm x 1200 mm (± 30 mm) were considered. The conventional vertical stacking technique was denoted as W1 and new propose techniques (cross laminated) was denoted as W2. Three replicates of each type were fabricated and tested under in-plane lateral load until failure. The test results revealed that, the wallettes fabricated using the new fabrication technique significantly increased two times in load carrying capacity compared to wallettes with conventional technique.